1954
DOI: 10.1002/pol.1954.120120119
|View full text |Cite
|
Sign up to set email alerts
|

A dielectric study of a carboxymethylcellulose in aqueous solution

Abstract: The dielectric properties of proteins in polar solvents have been extensively studied, and recently some linear polyelectrolytes-nucleic acids, nucleohistone, and hyaluronic acid-in polar solvents have been investigated at this l a b o r a t~r y .~-~ Most proteins studied have been highly polar and belong to the relatively small group of substances which give dielectric increments in solution. This is also the case for the linear macromolecules mentioned above, and these are still more polar so that they may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1955
1955
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 1 publication
2
9
0
Order By: Relevance
“…This theory appears at first sight attractive and has enjoyed some degree of acceptance [29], Two things, however, are wrong with it: (1) Some of these polymers, for example dextran [4][5][6][7], do not cause a decrease, but an increase in the f-potentials of cells as do also the strongly negatively charged nucleic acids [19]. (2) Albumin, although it increases the dielectric constant of water somewhat, is unlikely to cause increases to the extent noted by Pollack et al [42], see Oncley [31]; while dextran, being virtually apolar cannot and does not have any not able effect on the dielectric constant of wa ter at all [2,24].…”
Section: Electrokinetic Interactionsmentioning
confidence: 95%
“…This theory appears at first sight attractive and has enjoyed some degree of acceptance [29], Two things, however, are wrong with it: (1) Some of these polymers, for example dextran [4][5][6][7], do not cause a decrease, but an increase in the f-potentials of cells as do also the strongly negatively charged nucleic acids [19]. (2) Albumin, although it increases the dielectric constant of water somewhat, is unlikely to cause increases to the extent noted by Pollack et al [42], see Oncley [31]; while dextran, being virtually apolar cannot and does not have any not able effect on the dielectric constant of wa ter at all [2,24].…”
Section: Electrokinetic Interactionsmentioning
confidence: 95%
“…Allg6n and Roswall [11,12] and later Allen et al [13] observed a dielectric relaxation of aqueous CMC at 0.3 to 20 MHz. Their results suggest that our constant part of An at 100 kHz may relax with further increase of frequency above 100 kHz, which is denoted relaxation A in the following.…”
Section: General Behaviormentioning
confidence: 97%
“…According to the dielectric studies by Allg~n and Roswall [11] and Allen et al [13], the relaxational frequency fA is rather insensitive to molecular weight and increases with increasing Cp and Cs. Our results indicate that the relaxation strength 6(An)A levels off with increasing Cp.…”
Section: Relaxation Amentioning
confidence: 97%
See 1 more Smart Citation
“…Dielectric spectroscopy of aqueous solutions of NaCMC shows two dispersions: highfrequency [47] and low-frequency [48]; the presence of two dispersions is typical for polyelectrolytes. The high-frequency dispersion is independent on the contour length but the low-frequency is strongly dependent on it; on this base the two frequency regions are attributed to counterions moving along chain's parts or along the hole polyelectrolyte chain, respectively [49,50].…”
Section: Polarizability Of Cmc At Random Coil Conformationmentioning
confidence: 99%